The Role of Parents in Improving the Social Emotional Development of Early Childhood: A Systematic Literature Review - Istianti, Tuti; Halimah, Leli; AM, Muh. Asriadi; Fauziani, Lutfia (FKIP Universitas Lampung, 2023)
The Role of Parents in Improving the Social Emotional Development of Early Childhood: A Systematic Literature Review. The socio-emotional development of early childhood has a long-term impact on an individual's ability to interact socially and maintain emotional balance in later life. This research aims to examine the significance of parental roles in enhancing the socio-emotional development of young children. The study employs the Systematic Literature Review (SLR) method, collecting data through literature searches in various journals via databases like Google Scholar. Twenty five articles were analyzed. The research findings indicate several actions that parents should take to optimize the socio-emotional development of young children, including serving as primary educators, caregivers, and role models. Additionally, parents need to provide encouragement and create learning opportunities within their environment. In conclusion, collaborative efforts between fathers and mothers are essential for the optimal socio-emotional development of children. Keywords: early childhood, the role of parents, social-emotional development.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202314